Online writing task for young learners during MCO: pupils and parents responses - Senin, Muhammad Adam; Halim, Harliana; Ramdzan Ali, Al Amirul Eimer (2021)
Malaysia Movement Control Order (MCO) has encouraged the education system to move forward in the Information Communication and Technology (ICT) usage especially to communicate, receive and sending information including tasks among educators and students. However, writing skill task for young learners is not an easy task to be carried out online without a close supervision from the teacher. Writing skills among second language learners require full attention and guidance from the teacher in the classroom especially in term of the teaching and learning of grammar rules. This study focuses on analysing and determining the effectiveness on pupils respond towards a writing task given via online. Parents involvement in guiding their child in completing their task was analysed too. A qualitative research design by using document analysis based on the responses given by twenty randomly chosen 12 year-old pupils and parents in a primary school in Johor, Malaysia were used in this study. Narrative writing analysis were used to explain the outcome. The results given by the pupils to complete the task were excellent. They managed to complete the task within the time frame given. Parents play a major role in guiding their children to use the ICT gadgets such as smartphones, computers and laptops with proper internet connection to complete and submit their task accordingly. It is hope that this paper would encourage educators, parents and pupils to adapt the new norm situation by using ICT especially in writing task that was always and only conducted in the classroom.